National Campaign for Cerrado Defense:: an Experience that Emerges from Backlands Soil and Water (Élisée - Revista de Geografia da UEG, 2020)
This article is about an experience report of the work of the National Campaign for Cerrado Defense formed by more than 40 social organizations and it performed together with traditional communities of more than nine Brazilian States. The objective of this text is to present the campaign and its promotion actions for Cerrado biodiversity defense. To report that experience, there were made some information settings in the memories of the campaign encounters, in the leadership communities’ testimonials, and in the bibliographies related to the topic. In the dialogue about the campaign is evident that the challenge to protect cerrados territories is as bigger as its own territorial extension and wealth. The preservation of Cerrado is just possible with the guarantee of people’s rights and traditional communities to the territories, water, and food sovereignty. Finally, it is evident that people are in a constant struggle for Cerrado defense and count on women’s force and youth courage and audacity.
Keywords: Territories. Traditional People and Communities. Cerrado